Dietary Variations in a Multiethnic Parkinson’s Disease Cohort and Possible Influences on Nonmotor Aspects: A Cross-Sectional Multicentre Study - Anna Sauerbier; Anette Schrag; Pablo Martinez-Martin; Lynsey J. Hall; Miriam Parry; Laurie K. Mischley; Panagiotis Zis; K. Ray Chaudhuri (Parkinson's Disease)
Dietary habits may differ between Parkinson’s disease (PD) patients of different ethnicities. The primary aim of this cross-sectional analysis was to compare dietary habits in a multiethnic PD population and investigate potential nonmotor differences. All patients completed a dietary habits questionnaire. Besides basic demographics, patients’ motor involvement (Hoehn and Yahr (HY)) and nonmotor symptoms (Nonmotor Symptoms Scale; Hospital Anxiety and Depression Scale) were assessed. 139 PD patients were included (mean age 66.8 ± 11.6 years; 61.2% male; mean disease duration 6.2 ± 5.2 years; median HY 3): 47.5% were White, 24.5% Asian, and 28.0% Black African and Caribbean (BAC). We found dietary differences between the groups, including a greater frequency of vegetarians and greater consumption of cumin, turmeric, and cinnamon as well as lower consumption of beef in Asian patients than in White and BAC and greater consumption of chili than in White patients and higher consumption of pork in White than Asian and BAC patients. There were no significant differences in dietary supplement consumption after correction for multiple comparisons. None of the dietary factors examined were associated with differences in nonmotor symptoms. Diet and supplement use vary in PD patients across ethnicities, this is both a problem and opportunity for nutritional medicine research. These data support the importance of considering ethnic diversity as part of recruitment strategy in nutrition and clinical studies.